Panai Tradition in Bugis Makassar Society in Bima: Islamic Law Perspective - Amrin, Amrin; Sugiyarto, Sugiyarto; Amelia, Ishma (Al-Insyiroh: Jurnal Studi Keislaman, 2024)
This research aims to find out how the panai tradition of Islamic law is reviewed in the marriage traditions of the Bugis tribe of Makassar in Bima. This research uses descriptive qualitative research with a normative sociological approach to field studies. The collection techniques are observation, interviews and documentation. Meanwhile, data analysis processing techniques use reduction, data presentation and conclusions. The results of this research show that first, the Bugis Community in Makassar has two elements that cannot be separated in the marriage process, namely the man not only gives the dowry but also gives panai. If one of the parties commits a violation after the application and cash payment process has been carried out, then one of them will be subject to a fine. Second, judging from Islamic law, marriage is subject to the application of panai as one of the mandatory requirements in traditional marriages of the Bugis tribe which does not violate the pillars and conditions of marriage in Islamic law, because the tradition of giving panai is by the principles of Islamic marriage law because it contains the principle of consent and agreement between the groom and the bride in determining the value of the panai.